Primary diagnosis and length of Hospital stay of person with parkinson’s disease in a teaching Hospital: a cross-sectional study - J, Faeiz Syezri Adzmin; S, Norfarhana; A, Azimatun Noor; A, Fayiza Manzoor (Penerbit Universiti Kebangsaan Malaysia, 2023)
Parkinson’s disease (PD) is a progressive, chronic neurodegenerative condition associated with significant morbidity and mortality, specially more prevalent at age 65 years and above. Hence, an increase in life expectancy will also result in an increased prevalence of PD. Most of the PD management was done in outpatient settings. However, complications related to the disease progression may warrant admission. The study was done to determine the primary diagnosis and length of hospital stay of person with Parkinson’s (PwP) in a teaching hospital in Malaysia from 2010 to 2020. Data from the hospital information system, including patients’ diagnoses coded according to ICD-10, were used in the study. According to a study of 1587 patients, only 10.0% of PwP were primarily diagnosed with Parkinson’s disease, with a median length of stay of four days. 'Chapter X: Disease of the Respiratory System' was the most common among PwP which was not primarily diagnosed with PD. Four disease categories; 'Chapter I: Certain infectious and parasitic disease', 'Chapter V: Mental and behavioral disorders', 'Chapter XII: Diseases of the skin and subcutaneous tissue' and 'Chapter XIX: Injury, poisoning and certain other consequences of external cause’ are the diseases' that predicted to have a length of stay of more than 18 days. In conclusion, earlier detection of the disease complications may prevent hospitalisation, which may save a lot of hospital resources.